Winning Attitude A Pitching Coach's Lessons for Leaders - Klann, Gene (Center for Creative Leadership, 2001)
The coaching of executives continues to be a growing industry, but how often and how well do executives themselves coach as well as lead the people in their organizations? The system used by baseball's Johnny Sain offers a starting point for business leaders interested in developing this skill.
Online resource; Title from title page (viewed January 1, 2001)
Keywords: Electronic books; local